2018
DOI: 10.3390/app8112266
|View full text |Cite
|
Sign up to set email alerts
|

Design and Testing of a LUT Airfoil for Straight-Bladed Vertical Axis Wind Turbines

Abstract: The airfoil plays an important role in improving the performance of wind turbines. However, there is less research dedicated to the airfoils for Vertical Axis Wind Turbines (VAWTs) compared to the research on Horizontal Axis Wind Turbines (HAWTs). With the objective of maximizing the aerodynamic performance of the airfoil by optimizing its geometrical parameters and by considering the law of motion of VAWTs, a new airfoil, designated the LUT airfoil (Lanzhou University of Technology), was designed for lift-dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The four typical airfoils for VAWT are employed to study on dynamic characteristics of VAWT by using the improved LB model, they are NACA0018, S1046, DU06-W-200 (AACU, 2021), and LUT airfoil (Li et al, 2018), respectively. Among them, NACA0018 and S1046 are symmetric airfoils and are commonly used to VAWT, while DU06-W-200 and LUT airfoil are dedicated asymmetrical airfoils for VAWT.…”
Section: Resultsmentioning
confidence: 99%
“…The four typical airfoils for VAWT are employed to study on dynamic characteristics of VAWT by using the improved LB model, they are NACA0018, S1046, DU06-W-200 (AACU, 2021), and LUT airfoil (Li et al, 2018), respectively. Among them, NACA0018 and S1046 are symmetric airfoils and are commonly used to VAWT, while DU06-W-200 and LUT airfoil are dedicated asymmetrical airfoils for VAWT.…”
Section: Resultsmentioning
confidence: 99%
“…Since the efficiency of a VAT turbine is quite sensitive to the particular shape used for the hydrofoil [71], a qualitative assessment for the pressure coefficient for the baseline (symmetric) and cambered hydrofoils is performed to obtain a deeper understanding of this impact. The pressure coefficient over a hydrofoil can be determined by the pressure and stream properties as follows [72]: 14) where Qp: the pressure coefficient; P: the pressure; Pi: the freestream pressure.…”
Section: Fluid Physics Of the Baseline And Optimized Vat Turbinesmentioning
confidence: 99%
“…There are 2 papers dealing with the development of vertical axis wind turbines. Li et al [19] designed a Lanzhou University of Technology (LUT) airfoil for straight-bladed vertical axis wind turbines with an objective of maximizing its aerodynamic performance. Zhao et al [20] introduced a variable pitch approach for improving the performance of straight-bladed vertical axis wind turbine at rated tip-speed-ratio, and it was found that the new variable pitch approach can achieve an 18.9% growth of the peak power coefficient of the vertical axis wind turbine at the optimum tip-speed-ratio.…”
Section: Current Status In Wind Turbine Aerodynamicsmentioning
confidence: 99%